Promises to keep how Jackie Robinson changed America - Robinson, Sharon 1950- (New York Scholastic Press, 2004)
A biography of baseball legend Jackie Robinson, the first African American to play in the major leagues, as told by his daughter
Hurg
5
Keywords: African American baseball players -- Biography -- Juvenile literature; Baseball players -- Biography -- Juvenile literature